Safeguarding Nigeria: strategies for combating insurgency and terrorism (Law and Safety, 2024)
The paper appraises the strategic responses by Nigeria’s government to the intractable difficulties posed by insurgency, banditry, and terrorism experienced largely in its northern parts, identifying key initiatives such as the establishment of the 7th Division of the Nigerian Army, among other international and local collaborations and initiatives like the Civilian Joint Task Force. Another contentious issue is the vote of support by the National Assembly for a proposal to engage mercenaries in defence, reflecting the ongoing debate over security measures. The methodological approach of the paper is qualitative, with thematic analysis of data from secondary sources such as newspapers, books, and academic journals. The findings indicate that Nigeria’s security strategy is largely reactive, failing to address the fundamental root causes of violence, which are socio-economic disparities, political marginalisation, and historical grievances. The limitations of ad hoc security policies are evident; they tend to favour short-term solutions over long-term stability. Notably, it is such options for employing mercenaries that have been strongly challenged, especially regarding the implications of the alternatives on national sovereignty and in adequately addressing the root causes of such a challenge. In the absence of such a policy intervening into the root causes, which this study strongly calls for, inclusive national dialogue among and between the diverse ethnic groupings should be pursued. This could resolve not only the ethno-religious tensions that breed but also the systemic marginalisation of Nigeria’s diverse ethnic groups. The paper concludes by emphasising that what is needed is a coherent strategy beyond immediate security responses, which would integrate socio-economic development with good governance. It warns that unless these foundational issues are resolved, even if terrorism is resolved, the cycle of violence and the threat of separatist agitations will probably continue. A holistic approach toward national security is imperative for long-term peace and stability in Nigeria.
Keywords: strategies; security; insurgency; banditry; terrorism; countermeasures; peace and development.